Serum Anti-Müllerian Hormone Concentration in Young Women with Chronic Kidney Disease on Hemodialysis, and After Successful Kidney Transplantation - Ewelina Sikora-Grabka; Marcin Adamczak; Piotr Kuczera; Magdalena Szotowska; Paweł Madej; Andrzej Wiecek (Karger Publishers, 2016)
Background/Aims: In women with chronic kidney disease (CKD) fertility abnormalities occur frequently. Anti-Müllerian hormone (AMH) inhibits excessive recruitment of primordial follicles. The aim of the study was to evaluate the serum AMH concentration in women on hemodialysis and after kidney transplantation (KTx). Methods: 46 hemodialysed women and 14 with CKD about to undergo kidney transplantation were enrolled into the study. The control group consisted of 40 healthy women. In all subjects serum concentration of AMH was determined (in chronic hemodialysis women and in control group once, and in women after KTx immediately before surgery, and 3 times after the transplantation). Results: Serum AMH concentration in hemodialysed women and in the control group did not differ significantly, while in hemodialysed women with regular menstrual cycles it was significantly lower than in the control group: 2.20 (1.08-3.55ng/ml) and 3.30 (1.80-6.10ng/ml) respectively, (p=0.02). In the KTx group, a significant decrease in serum AMH concentration was found from 3.30ng/ml (2.20-6.50ng/ml) at baseline to 1.90ng/ml (1.30-2.40ng/ml) at 6 months after KTx (p=0.007). Conclusions: 1. Significantly lower serum AMH concentration was found in the regularly menstruating CKD women on hemodialysis in comparison with the healthy controls. 2. Serum AMH decreased significantly after successful KTx.